Activation of Reduced-Graphene-Oxide Supported Pt Nanoparticles by Aligning with WO3-Nanowires toward Oxygen Reduction in Acid Medium: Diagnosis with Rotating-Ring-Disk Voltammetry and Double-Potential-Step Chronocoulometry. Issue 15 (1st January 2018) - Rutkowska, Iwona A.; Wadas, Anna; Zoladek, Sylwia; Skunik-Nuckowska, Magdalena; Miecznikowski, Krzysztof; Negro, Enrico; Noto, Vito Di; Zlotorowicz, Agnieszka; Zelenay, Piotr; Kulesza, Pawel J.
Abstract : The chemically-reduced graphene-oxide has been used as support to anchor catalytic Pt nanoparticles and, while subsequently modified with tungsten oxide nanowires, has produced a hybrid electrocatalytic system for electroreduction of oxygen in acid medium. Such characteristics of reduced graphene oxide as defective surface and low degree of organization of graphitic structures facilitate dispersion of platinum nanocenters. Further combination with WO3 nanonowires is expected to increase the system's interfacial hydrophilicity and porosity. Most likely WO3 nanostructures are attached mainly to the edges of graphene thus preventing its stacking and creating space for the flux of oxygen and the reaction products. The results of electrochemical diagnostic experiments are consistent with the view that the electrocatalytic activity of the system utilizing tungsten oxide nanowires toward the reduction of oxygen in acid medium has been enhanced even at the Pt loading as low as 30 μg cm −2 . Furthermore, the rotating ring-disk electrode voltammetry data is consistent with decreased formation of the undesirable hydrogen peroxide intermediate in the presence of WO3 . The conclusions are supported with mechanistic and kinetic studies performed with use of double-potential-step chronocoulometry as an alternative diagnostic tool to rotating ring-disk voltammetry.